Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

What is the solution set of (x - 2)(x - 3) = 2?
{1, 4}
{2, 3}
{4, 5} **Weegy:** y= -3x/2 **User:** What is the value of b2 - 4ac for the following equation?
2x2 + 3x = -1
0
1
17 **Weegy:** The answer is: b.1 [smile] **User:** Write the quadratic equation in factored form. Be sure to write the entire equation.
x2 + x - 12 = 0 **Weegy:** (x+4)(x-3)=0 **User:** Which of the following equations is the result of completing the square on x2 - 6x - 9 = 0?
(x - 3)2 = 0
(x - 3)2 = 9
(x - 3)2 = 18 **Weegy:** (x-3)^2=18 **User:** What is the solution set of 2x(x - 1) = 3 **Weegy:** x = -14/11 **User:** An object is dropped off a building that is 144 feet tall. After how many seconds does the object hit the ground? (s = 16t2)
3 seconds
4 seconds
9 seconds **Weegy:** Thea answer is a.3 seconds **User:** The width and the length of a rectangle are consecutive even integers. If the width is decreased by 3 inches, then the area of the resulting rectangle is 24 square inches. What is the area of the original rectangle?
12 square inches
48 square inches
96 square inches **Weegy:** The width and the length of a rectangle are consecutive even integers. If the width is decreased by 3 inches, then the area of the resulting rectangle is 24 square inches. What is the area of the original rectangle? B. [ 48 square inches
] **User:** Which of the following constants can be added to x2 - 10x to form a perfect square trinomial?
10
25
100 **Weegy:** The answer is 1/4.
Here, I'll show you how to get that answer:
Trial and Error Method:
1) 1/4, [ 1/2 and 1 are the possible answers in the choices but we know that 1/2 is not a perfect square so it's not possible for 1/2 to be the answer.
2) Now try 1/4 and 1 and add them to the equation to get:
x2 - x + 1/4
x2 - x + 1
3)Use the perfect square formula if you can:
x2 - x + 1/4 becomes (x-1/2)2? Yes!
x2 - x + 1 becomes (x-1)2 ...No! that's wrong because (a-b)2 = a2-2ab +b2
Thus, 1/4 is the answer.
Easy Formula Method:
1) In a perfect square trinomial, c = (b/2a)2.
a=1 because it's the co-efficient of x2
b=1 because it's the ... (More)

Question

Not Answered

Updated 7/2/2014 3:02:34 AM

5 Answers/Comments

(x - 2)(x - 3) = 2

x^2 - 3x - 2x + 6 = 2

x^2 - 5x + 4 = 0

(x - 1)(x - 4) = 0

x = 1 or x = 4

The solution set of (x - 2)(x - 3) = 2 is {1, 4}

x^2 - 3x - 2x + 6 = 2

x^2 - 5x + 4 = 0

(x - 1)(x - 4) = 0

x = 1 or x = 4

The solution set of (x - 2)(x - 3) = 2 is {1, 4}

Added 7/2/2014 2:45:51 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/2/2014 3:24:17 AM]

2x(x - 1) = 3

2x^2 - 2x - 3 = 0

a = 2, b = -2, c = -3

b^2 - 4ac = (-2)^2 - 4(2)(-3) = 4 + 24 = 28

x = (2 ± sqrt 28)/4

= (2 ± 2 sqrt 7)/4

= (1 ± sqrt 7)/2

2x^2 - 2x - 3 = 0

a = 2, b = -2, c = -3

b^2 - 4ac = (-2)^2 - 4(2)(-3) = 4 + 24 = 28

x = (2 ± sqrt 28)/4

= (2 ± 2 sqrt 7)/4

= (1 ± sqrt 7)/2

Added 7/2/2014 2:49:08 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/2/2014 3:24:40 AM]

y(y + 4)(y - 6) = 0 is a quadratic equation. FALSE.

y(y + 4)(y - 6) = 0

y(y^2 - 2y - 24) = 0

y^3 - 2y^3 - 24y = 0 which is not a quadratic equation.

y(y + 4)(y - 6) = 0

y(y^2 - 2y - 24) = 0

y^3 - 2y^3 - 24y = 0 which is not a quadratic equation.

Added 7/2/2014 2:52:25 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/2/2014 3:24:48 AM]

The radius of the circle whose equation is x^2 + y^2 = 9 is 3.

Added 7/2/2014 3:01:16 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/2/2014 3:25:06 AM]

y(y + 4) - y = 6 is a quadratic equation.
True
False User: A circle has a diameter with endpoints of (-2, 8) and (6, 4). What is the center of the circle?
(8, 12)
(4, 12)
(2, 6) **Weegy:** Diameter=10.198
center=(2,6) **User:** Which of the following equations has only one solution?
x 2 = 9
x(x - 1) = 9
x 2 - 6x + 9 = 0 **Weegy:** 6x - 5 = -17 solution is x = -2. Click on the "Good" button. Thank you. **User:** Which of the following equations is of a parabola with a vertex at (1, 2)?
y = (x - 1) 2 - 2
y = (x - 1) 2 + 2
y = (x + 1) 2 - 2
y = (x + 1) 2 + 2 **Weegy:** A parabola whose equation is y = (x - 5)2 - 2 has a vertex at (5,-2).
**User:** Which of the following constants can be added to x 2 - x to form a perfect square trinomial?
1/4
1/2
1 **Weegy:** The answer is 1/4.
Here, I'll show you how to get that answer:
Trial and Error Method:
1) 1/4, [ 1/2 and 1 are the possible answers in the choices but we know that 1/2 is not a perfect square so it's not possible for 1/2 to be the answer.
2) Now try 1/4 and 1 and add them to the equation to get:
x2 - x + 1/4
x2 - x + 1
3)Use the perfect square formula if you can:
x2 - x + 1/4 becomes (x-1/2)2? Yes!
x2 - x + 1 becomes (x-1)2 ...No! that's wrong because (a-b)2 = a2-2ab +b2
Thus, 1/4 is the answer.
Easy Formula Method:
1) In a perfect square trinomial, c = (b/2a)2.
a=1 because it's the co-efficient of x2
b=1 because it's the coefficient of x
c=? and it's the missing constant
using the formula and the given, c = 1/4.
That's it! :D Good Luck!
] **User:** Write the quadratic equation in general form. What is the value of b 2 - 4ac?
1 = 2x 2 + 7x
40
41
57 **User:** The graph of y = ax 2 + bx + c is a parabola that opens up and has a vertex at (-2, 5). What is the solution set of the related equation 0 = ax 2 + bx + c?
{-2}
{5} (More)

Question

Not Answered

Updated 7/2/2014 11:30:10 PM

4 Answers/Comments

y(y + 4) - y = 6 is a quadratic equation. True.

y(y + 4) - y = 6

y^2 + 4y - y = 6

y^2 + 3y - 6 = 0 which is a quadratic equation.

y(y + 4) - y = 6

y^2 + 4y - y = 6

y^2 + 3y - 6 = 0 which is a quadratic equation.

Added 7/2/2014 11:25:25 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/2/2014 11:26:49 PM]

The equation that has only one solution is x^2 - 6x + 9 = 0

Added 7/2/2014 11:26:15 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/2/2014 11:27:04 PM]

The equation of a parabola with a vertex at (1, 2) is: y = (x - 1)^2 + 2

Added 7/2/2014 11:26:57 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/2/2014 11:30:45 PM]

27,384,213 questions answered

There are no comments.